2010
DOI: 10.1021/jm100499s
|View full text |Cite
|
Sign up to set email alerts
|

Thiadiazole Carbamates: Potent Inhibitors of Lysosomal Acid Lipase and Potential Niemann−Pick Type C Disease Therapeutics

Abstract: Niemann-Pick type C (NPC) disease is a lysosomal storage disorder characterized at the cellular level by abnormal accumulation of cholesterol and other lipids in lysosomal storage organelles. Lysosomal acid lipase (LAL) has been recently identified as a potential therapeutic target for NPC. LAL can be specifically inhibited by a variety of 3,4-disubstituted thiadiazole carbamates. An efficient synthesis of the C(3) oxygenated/C(4) aminated analogues has been developed that furnishes the products in high yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 33 publications
4
58
1
Order By: Relevance
“…Inhibition of LAL increases insulin secretion To characterise the role of LAL in beta cell function more comprehensively, and to avoid confounding effects of incomplete gene knockdown, we employed Lalistat, an inhibitor that is highly specific for LAL over neutral lipases [23,31,32]. Lalistat pretreatment for 24 h dose dependently increased insulin secretion from MIN6 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of LAL increases insulin secretion To characterise the role of LAL in beta cell function more comprehensively, and to avoid confounding effects of incomplete gene knockdown, we employed Lalistat, an inhibitor that is highly specific for LAL over neutral lipases [23,31,32]. Lalistat pretreatment for 24 h dose dependently increased insulin secretion from MIN6 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CE would have to be hydrolyzed by lipases in the lysosomes to produce cholesterol. However, we found that lalistat 1, a lysosomal lipase inhibitor (20), had a limited impact on nutrientdependent changes in ER cholesterol (Fig. S5A).…”
Section: Mtorc1 Activates Srebp-2 By Inhibiting Cholesterol Traffickimentioning
confidence: 94%
“…Lalistat (lalistat-2; 3,4-disubstituted thiadiazole carbamate, compound 12 from Rosenbaum et al (21), was a gift from Paul Helquist (University of Notre Dame). The pyrazole-methanone compounds E4, F2, and H4 were described in VanderVen et al (23).…”
Section: Reagentsmentioning
confidence: 99%